(untitled) (Research, Society and Development, 2022)
Dentin hypersensitivity (DH) is a common painful clinical condition, usually associated with exposed dentin surfaces, which cause your tubular system to be open. This causes fluid movement and activates a neural response in the pulp. Although it is one of the most common patient complaints, there are no universally accepted guidelines for differential diagnosis, nor reliable treatment modalities. In addition, the mechanisms by which the different materials act are still not very clear and this knowledge is essential for a safe and effective treatment. The objective of this literature review was, through a scientific search in databases (PubMed e Google Scholar) and a knowledge of basic chemistry, to explain some chemical mechanisms involved in the mineralization and demineralization of dentin and the action of different compounds used in HD treatment, supporting professionals to find the best treatment for each patient.